Effect of Doses of Lecanicillium Lecanii on the Controlling of Rice Bug in Rice Plants - Nurlina Nurlina; Sri Purwanti; Sri Hidayati; Bambang Gunawan; Mahrus Ali (Universitas Panji Sakti, 2022)
Bug is an important pest of rice plants because it can reduce the quality and quantity of production, so it is essential to control its population. One of the efforts to control rice bugs is to use the biological agent Lecanicillium lecanii because it does not cause resistance and is not harmful to human health. This study aims to determine the effect of the number of doses of Lecanicillium lecanii application in controlling the pest population of walang sangit (rice bugs) in rice cultivation. The research method used a completely randomized design (CRD) with four treatment doses of the biological agent Lecanicillium lecanii with a rank of 9 x 107. P0 without biological agent treatment, P1 = using a biological agent with a dose of 10 ml.L-1 of water, P2 = using biological agent with a doses of 12.5 ml.L-1 of water, P3 = using biological agent with a dose of 15 ml.L-1 of water, and. Each treatment was repeated 4 times. The results of the study The application dose of 15 ml.L-1 gave the best results, and this is in accordance with the recommendations of BBPOPT Jatisari that the application dose of Lecanicillium lecanii is 15 ml.L-1 .